Potential pathways to HIV/AIDS transmission in the Niger Delta of Nigeria: Poverty, migration and commercial sex - Udoh, IA (2009)
HIV prevalence in the Niger Delta of Nigeria is generally attributed to concurrent sexual partnerships and weak public sector health care and education systems. This paper examines the likelihood of additional factors, such as the intersection of widespread poverty, migration, and sex work, as contributory channels of HIV transmission in the region. To explore this issue, we conducted a Delphi survey with 27 experts to formulate consensus about the impact of poverty, migration, and commercial sex on AIDS in the Niger Delta. Results suggest that these factors and others have exacerbated the epidemic in the region. To stop the further spread of HIV in the region, efforts to address poverty, sex work, and multiple sexual partnerships require building a public-private partnership which involves participatory action strategies among key stakeholders.